2017
DOI: 10.1111/iwj.12856
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for deep surgical site infection after open reduction and internal fixation of closed tibial plateau fractures in adults

Abstract: This study aimed to investigate the incidence and risk factors of deep surgical site infection (DSSI) during hospitalisation after closed tibial plateau fractures treated with open reduction and internal fixation (ORIF). We performed this retrospective study at a university-affiliated hospital with an advanced trauma centre. The data of adult patients with closed tibial plateau fractures treated with ORIF from January 2012 to February 2017 were extracted from the electronic medical records. Demographics, injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Following the removal of duplicate studies, a total of 4472 studies were available for title and abstract screening (Figure 1). With our inclusion criteria applied and relevant reference lists screened, 117 studies 1,2,4,5,10,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…Following the removal of duplicate studies, a total of 4472 studies were available for title and abstract screening (Figure 1). With our inclusion criteria applied and relevant reference lists screened, 117 studies 1,2,4,5,10,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had been conducted to investigate the incidence and related risk factors of SSI, including the extended operation time, smoking status, open fracture type, higher level of fracture type (Schatzker types IV-VI), and so on [5][6][7][8]. However, most previous researches were designed as a retrospective, which might have limitations inaccuracy of data collection and obscure follow-up information.…”
Section: Introductionmentioning
confidence: 99%
“…Among the complications, SSI was the most common one. Previous literature had reported that SSIs developed at 2–14.2% of patients after they underwent ORIF, half of which were deep infections [ 5 7 ]. Consequently, patients had to be re-admitted or even re-operated to replace or remove internal fixtures to treat the infection.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4], Among the complications, SSI was the most common one. Previous literature had reported that SSIs developed at 2-14.2% of patients after they underwent ORIF, half of which were deep infections [5][6][7]. Consequently, patients had to be re-admitted, or even re-operated to replace or remove internal fixtures to treat the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had been conducted to investigate the incidence and related risk factors of SSI, including the extended operation time, smoking status, open fracture type, higher level of fracture type (Schatzker types IV-VI), and so on [5][6][7][8]. However, most previous researched were designed as retrospective, which might have limitations inaccuracy of data collection and obscure follow-up information.…”
Section: Introductionmentioning
confidence: 99%